As We Have Always Done: Indigenous Freedom Through Radical Resistance - Simpson, Leanne Betasamosake (Indigenous Americas, 2017)
Across North America, Indigenous acts of resistance have in recent years opposed the removal of federal protections for forests and waterways in Indigenous lands, halted the expansion of tar sands extraction and the pipeline construction at Standing Rock, and demanded justice for murdered and missing Indigenous women. In As We Have Always Done, Leanne Betasamosake Simpson locates Indigenous political resurgence as a practice rooted in uniquely Indigenous theorizing, writing, organizing, and thinking. Indigenous resistance is a radical rejection of contemporary colonialism focused around refusing the dispossession of Indigenous bodies and land. Simpson makes clear that the resistance's goal can no longer be cultural resurgence as a mechanism for inclusion in a multicultural mosaic. Instead, she calls for unapologetic, place-based Indigenous alternatives to the destructive logics of the settler colonial state, including heteropatriarchy, white supremacy, and capitalist exploitation. --Publisher's description.
Keywords: Activism. Ojibwa; Canada; Government relations; Government relations. Ojibwa Indians; Ojibwa Indians; Politics and government. Ojibwa; Politics and government. Ojibwa Indians